Do adolescents with different types and degrees of idiopathic scoliosis curves differ in postural control compared to their healthy peers? a cross-sectional study - Mohammad Bayattork; Zohreh Yaghoubitajani; Josette Bettany-Saltikov (BMC Musculoskeletal Disorders)
Abstract Background Numerous scoliosis research studies have investigated postural control changes in adolescents with idiopathic scoliosis and compared them to healthy controls. However, the results have been controversial. Therefore, the present study aimed to compare whether postural control in adolescent idiopathic scoliosis (AIS) patients is different from their age-matched healthy counterparts. Methods An exploratory cross-sectional study was conducted comprising 121 adolescents (11 to 17 years) divided into five groups, including those diagnosed with idiopathic scoliosis (n = 95) and healthy control peers (n = 26). According to the type (single or double), location (thoracic or lumbar), and severity (mild = Cobb's angle ≤ 25°, moderate = 26° ≤ Cobb's angle ≥ 45°) of AIS, the groups included: group 1: mild single curve in the thoracic region, group 2: mild single curve in the lumbar region, group 3: mild double curves, group 4: moderate double curves, and group 5: healthy control. Computerized Dynamic Posturography (CDP)/ /NeuroCom International, Inc., Clackamas, OR, USA was used to assess the postural control parameters. The assessment included the Sensory Organization Test (SOT), the Adaptation Test (ADT), the Motor Control Test (MCT), the Weight-Bearing Squat test (WBS), and finally the Unilateral Stance Test (UST). Results The study analyzed data from 121 participants (36 boys, 85 girls) across five groups. No significant differences were found between the AIS and control groups concerning the type of curve or when comparing single and double curves. A one-way ANOVA indicated that variables related to the SOT were normally distributed, while other tests did not show normal distribution. Comparisons controlled for BMI, curve type (single or double), and severity of the major curve revealed no significant differences in postural control variables between AIS and control groups. Notable p-values include SOT 1 (p = 0.964), SOTstrategy 1 (p = 0.192), SOT 2 (p = 0.733), SOTstrategy 2 (p = 0.497), SOT 3 (p = 0.057), SOTstrategy 3 (p = 0.693), MCT (p = 0.089), USleftOpen (p = 0.087), and USrightOpen (p = 0.057). Conclusion This study's findings indicated that there were no statistically significant differences in postural control when performing activities of daily living among adolescents with idiopathic scoliosis compared to their healthy aged-matched peers. Therefore, there is no need for additional training to improve postural control in these adolescents with idiopathic scoliosis. However, the importance of identifying the postural control mechanisms in these populations is considerable for treating scoliosis.